Meningkatkan Kemampuan Membaca Permulaan melalui Media Kartu Huruf pada Anak Usia Dini - Fadhila, Luthfia Rizka; Sitorus, Ahmad Syukri (Absorbent Mind, 2026)
The purpose of this research is to analyse how RA BKM Nurul Iman's letter card program has helped students in grades 3-5 develop their reading abilities. The premise of this study is that kids nowadays still have a hard time with basic reading skills like word recognition, letter shape discrimination, and symbol recognition. This study used Classroom Action Research (CAR), which consisted of two cycles and involved twenty students. In order to quantify the attainment of developmental indicators, data was collected by observation, performance assessment, and documentation. The data was then analysed using descriptive quantitative methodologies with percentage calculations. The findings show that early reading skills increase with time. No student achieved the anticipated level of growth during the pre-cycle period. Initial progress in letter symbol and sound recognition followed the introduction of letter card media in Cycle I. In Cycle II, there was a more noticeable improvement; all pupils reached the desired developmental level, showing improved skills in letter identification, symbol-sound association, and reading short sentences. To sum up, letter cards are a great tool for helping young children develop their reading abilities. Promoting early literacy development and enhancing children's active engagement in the learning process, this media offers tangible, captivating, and participatory learning opportunities.